The effect 0f pyrogallol 0n the ph of plasmodium falciparum digestive vacuole - Omar, Alfaqih Hussain (2020)
Quercus infectoria, a highly potent medicinal herb is widely used in a Malay culture in several applications. Previous studies proved the antimalarial activity of Q. infectoria, however the exact phytochemical constituents leading to the antimalarial activity of this plant remains searchable despite years of intensive research efforts. It has been reported that pyrogallol is found among the phytoconstituents of Q. infectoria. Pyrogallol, an organic compound, has a capability of generating free radicals like other antimalarial drugs such as artemisinin. This has made artemisinin an acceptable drug to predict the mechanism of action of pyrogallol against P. falciparum in this study. It has been reported that reactive oxygen species (ROS) generated by artemisinin in the parasite’s digestive vacuole through endoperoxide bridge activation may cause parasite death. Another study reported that artemisinin displays direct inhibition of V-type H+-ATPase, a proton pump located on the digestive vacuole’s membrane in which the inactivation might cause pH alteration of this organelle. Hence, the flow cytometry-based assay was performed to measure the digestive vacuole pH after treatment with pyrogallol and artemisinin. The malarial SYBR Green 1 fluorescence-based (MSF) assay was used to determine the antimalarial activity of pyrogallol against the chloroquine-sensitive strain (3D7) of P. falciparum by determining the 50% inhibitory concentration (IC50). A pH calibration curve was constructed by using fluorescein isothiocyanate (FITC)-dextran, a ratiometric pH indicator incorporated into the digestive vacuole of isolated trophozoite stage parasites suspended in buffers of various pH values in the presence of an ionophore, carbonyl cyanide m-chlorophenylhydrazone (CCCP). The CCCP-free parasite displayed the steady-state digestive vacuole pH of 5.42 ± 0.11, hence validating the potential application of the generated pH calibration curve. Subsequently, the concentrations of IC50-4 hours (60 nM) and near IC50-4 hours (15 and 30 nM) of artemisinin were selected from the previous study to ensure the pH change of the digestive vacuole observed in the subsequent experiment was not resulted from parasite death. The assay of 4-hour drug pulse with artemisinin (15, 30 and 60 nM) was carried out by using mid trophozoite stage parasites to determine the pH change of the digestive vacuole. The selected concentrations of artemisinin increased the pH of the digestive vacuole by 1 (15 nM, pH = 6.6 ± 0.1), 1.48 (30 nM, pH = 7.1 ± 0.08) and 1.6 pH unit (60 nM, pH = 7.3 ± 0.1), respectively as compared with the untreated digestive vacuole (pH = 5.6 ± 0.1). The same result of the pH change of the digestive vacuole induced by a standard proton pump inhibitor, concanamycin A was observed. The result indicates that artemisinin might inhibit the V-type H+-ATPase, causing the pH change of the digestive vacuole. In conclusion, this study contributes to a better understanding on the mechanism of action of pyrogallol based on the results obtained by using artemisinin as a drug to predict the compound’s activity.